2021
DOI: 10.1038/s43247-021-00248-x
|View full text |Cite
|
Sign up to set email alerts
|

An extremeness threshold determines the regional response of floods to changes in rainfall extremes

Abstract: Precipitation extremes will increase in a warming climate, but the response of flood magnitudes to heavier precipitation events is less clear. Historically, there is little evidence for systematic increases in flood magnitude despite observed increases in precipitation extremes. Here we investigate how flood magnitudes change in response to warming, using a large initial-condition ensemble of simulations with a single climate model, coupled to a hydrological model. The model chain was applied to historical (19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(67 citation statements)
references
References 77 publications
3
64
0
Order By: Relevance
“…Bertola et al (2020Bertola et al ( , 2021 showed that the 100-year flood changed differently than the 2-year flood in some European regions and that these changes can be attributed to different drivers. Similarly, recent studies have shown that small and large floods respond differently to changes in precipitation (Brunner et al, 2021;Wasko et al, 2019Wasko et al, , 2021.…”
Section: Clarifying the Effects Of Temporal Changes On Upper Flood Tailsmentioning
confidence: 85%
“…Bertola et al (2020Bertola et al ( , 2021 showed that the 100-year flood changed differently than the 2-year flood in some European regions and that these changes can be attributed to different drivers. Similarly, recent studies have shown that small and large floods respond differently to changes in precipitation (Brunner et al, 2021;Wasko et al, 2019Wasko et al, , 2021.…”
Section: Clarifying the Effects Of Temporal Changes On Upper Flood Tailsmentioning
confidence: 85%
“…Recent evidence suggests that increases in western United States flood risk caused by anthropogenic warming may have been counteracted in recent decades by natural variability, but that further warming and shifts in natural variability will eventually “unmask” this accumulated increase in regional flood risk ( 51 ). Additional work suggests that the response of flood risk to climate change is likely to exhibit threshold behavior, at least in certain climatological and hydrological regimes ( 52 ), with a precipitation extremeness threshold dictating whether flood risk decreases (for smaller events, due to the antecedent soil aridification effect of warming temperatures) or increases (for the largest events, due to the overwhelming effect of large increases in precipitation intensity). Both of these considerations are especially germane to California—a region where most contemporary public policy and climate adaptation efforts emphasize drought and wildfire risk due to lack of recent experience with widespread severe floods.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since a warmer atmosphere holds more water vapor that can rain out, climate change also increases the frequency and intensity of extreme rainfall (Kirchmeier-Young & Zhang, 2020; Madakumbura et al, 2021;Myhre et al, 2019;Tan et al, 2021;Zhan et al, 2020), which in some locations can lead to an increased chance of floods occurring or an increase in their magnitude (Brunner et al, 2021;Sharma et al, 2018;Wasko et al, 2021).…”
Section: Individual Effect Of Ti Slr and Ri On Coastal-fluvial Floodsmentioning
confidence: 99%